Steamship DOLPHIN at dock in Skagway, ca. 1912 - Thwaites, John E. (John Edward), 1863-1940 (1912)
Caption on image: Skagway, Alaska PH Coll 247.603 The iron-hulled passenger steamer DOLPHIN of the Alaskan Steamship Company was built in 1892. She was sold to South American owners in 1917.